As transformações históricas e a dinâmica atual da paisagem na bacia hidrográfica do ribeirão Biguaçu - Apucarana/PR - Faria, Maria do Carmo Carvalho (2007)
With intention to stimulate the debate on the subject, this work has as object the Biguassu Brook hydrographic basin, located in Apucarana, Paraná, in objective one two questions are approached: to identify of the historical transformations occurred during the occupation process and its dynamics. Regarding to the landscape concept, it assumes the systemic boarding defended by G. Bertran (1968), who defined the landscape as a dynamic, unstable combination supported on three differentiated geographic elements - physical, biological and anthropic ones. It is necessary to consider that the construction of this research covers varied documents and studies. At first it is looked to establish a dialogue with the theoretical boarding concernin the landscape, that it consists of to define the concepts that will guide the presented quarrels. The bibliographical revision of the theme and the process in which the region goes by, what allows recognizing different reflections and clippings, establishes connections between these inquiries and the matter of this study. For time-space analysis we opted to the production and interpretation of letters of use the ground at three moments (1970, 1990 and 2006). Such current letter and photographic registers have given subsides to the physical study and of devolution of the dynamics of occupation and the forms of use of the ground as well as its scenery alterations between 1970 and 2006. This research, structures itself in six chapters, starting from as introduction to the research in a preliminary boarding of the Biguassu Brook hydrographic basin. Afterwards we show the theoretical quarrel of the relation between geography and landscape, aiming at identifying the concepts that had constituted the arguments of this quarrel. In a time-space boarding, supported on the bibliography, the third chapter has developed, with Paraná sociospace formation since earlier times until the current and this way is proven as the occupation of the occupation of the northen Paraná occurred through the colonizing Northen Paraná Land Company (CTNP) and its successor Paraná Improvement Company (CMNP) and, as important part of this process, the city of Apucarana. In the fourth chapter we present a brief study of the city, with emphasis in the Biguassu Brook hydrographic basin, approaching its geographic situation, its aspects (physiographic) and its description and morfometrical analysis. It is looked to detach its process of occupation and development, being analyzed and interpreted the use letters of the soil of 1970, 1990 and 2006, observing the occurred transformations in theses periods. Deepening the analysis of the anthropic action in the area, a photographic register will constitute the fifth chapter. In it, through a photo-interpretative work, we try to demonstrate the current conditions of the landscape in the basin displaying the economic and, mainly, the socioenvironmental conditions of the area. The sixth chapter presents the conclusions in which we present possible answers to the objective defined in the beginning of the researchWith intention to stimulate the debate on the subject, this work has as object the Biguassu Brook hydrographic basin, located in Apucarana, Paraná, in objective one two questions are approached: to identify of the historical transformations occurred during the occupation process and its dynamics. Regarding to the landscape concept, it assumes the systemic boarding defended by G. Bertran (1968), who defined the landscape as a dynamic, unstable combination supported on three differentiated geographic elements - physical, biological and anthropic ones. It is necessary to consider that the construction of this research covers varied documents and studies. At first it is looked to establish a dialogue with the theoretical boarding concernin the landscape, that it consists of to define the concepts that will guide the presented quarrels. The bibliographical revision of the theme and the process in which the region goes by, what allows recognizing different reflections and clippings, establishes connections between these inquiries and the matter of this study. For time-space analysis we opted to the production and interpretation of letters of use the ground at three moments (1970, 1990 and 2006). Such current letter and photographic registers have given subsides to the physical study and of devolution of the dynamics of occupation and the forms of use of the ground as well as its scenery alterations between 1970 and 2006. This research, structures itself in six chapters, starting from as introduction to the research in a preliminary boarding of the Biguassu Brook hydrographic basin. Afterwards we show the theoretical quarrel of the relation between geography and landscape, aiming at identifying the concepts that had constituted the arguments of this quarrel. In a time-space boarding, supported on the bibliography, the third chapter has developed, with Paraná sociospace formation since earlier times until the current and this way is proven as the occupation of the occupation of the northen Paraná occurred through the colonizing Northen Paraná Land Company (CTNP) and its successor Paraná Improvement Company (CMNP) and, as important part of this process, the city of Apucarana. In the fourth chapter we present a brief study of the city, with emphasis in the Biguassu Brook hydrographic basin, approaching its geographic situation, its aspects (physiographic) and its description and morfometrical analysis. It is looked to detach its process of occupation and development, being analyzed and interpreted the use letters of the soil of 1970, 1990 and 2006, observing the occurred transformations in theses periods. Deepening the analysis of the anthropic action in the area, a photographic register will constitute the fifth chapter. In it, through a photo-interpretative work, we try to demonstrate the current conditions of the landscape in the basin displaying the economic and, mainly, the socioenvironmental conditions of the area. The sixth chapter presents the conclusions in which we present possible answers to the objective defined in the beginning of the research